Analisis Stabilitas Dinding Penahan Tipe Kantilever Pada Landfill Tepi TPA Kota Masohi Kabupaten Maluku Tengah Provinsi Maluku - Erwin Syaiful Wagola; Mentari Rasyid (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
The construction of a retaining wall must be based on a stability calculation and safety factors because errors that occur can be no good. A retaining wall construction can be said to be safe if it is fulfilled. The purpose of this study was to analyze the stability of cantilever type soil retaining walls against shifting, overturning, and soil bearing strength. overturning, and strongly supporting the soil. The method of collecting and collecting data in the field used the field observation method.Wall stability analysis using analytical methods and numerical based software assistance. The results of data analysis show that the stability of the wall is safe against shear forces, rolling forces and the carrying capacity of the soil with a Safety Factor value of 4.05, 1.50, and 4.67.While the Out Put results from the application also show that the retaining wall at the Masohi City Landfill is still quite safe with a Safety Factor value of 1.80. Key Word: Cantilever, Landfill, Rolling, Shift, Safety Factor